CONSTITUTIONAL INTERPRETATION: THE CONSTITUTIONAL COURT'S PARADIGM SHIFT IN THE JUDICIAL REVIEW OF PRESIDENTIAL AND VICE-PRESIDENTIAL CANDIDACY THRESHOLD NORMS IN INDONESIA - Ekho Pratama; Slamet Suhartono; Miftahul Munir (Journal of International Islamic Law, Human Right and Public Policy, 2026)
The presidential threshold provision under Article 222 of Law No. 7 of 2017 on General Elections has generated prolonged debate concerning the inclusivity of electoral competition and the integrity of the presidential system. For over a decade, the Constitutional Court consistently upheld this norm as an open legal policy of the legislature. However, a fundamental shift occurred through Decision No. 62/PUU-XXII/2024, which declared the provision unconstitutional. This study analyzes the structure of the Constitutional Court's legal arguments in its prior jurisprudence and examines the legal rationale underlying the paradigm shift in this recent decision. This is a normative legal study employing statutory, case, and conceptual approaches. The findings indicate that the earlier jurisprudence relied on judicial restraint to maintain government stability and promote the simplification of the political party system. In contrast, Decision No. 62/PUU-XXII/2024 applies the doctrine of responsive judicial review, emphasizing substantive justice, the restoration of popular sovereignty, equality among political parties participating in the current general election, and the determination of the framers' original intent. The invalidation of this norm creates a technical legal vacuum, requiring the legislature to restructure the regulatory framework through new constitutional engineering for the 2029 General Election. This restructuring must combine the guarantee of inclusive rights—free from percentage thresholds—with a mandatory nomination mechanism to preserve stable and democratic electoral management.